2022
DOI: 10.1155/2022/5665408
|View full text |Cite
|
Sign up to set email alerts
|

Secure and Scalable Healthcare Data Transmission in IoT Based on Optimized Routing Protocols for Mobile Computing Applications

Abstract: The Internet of Things (IoT) has impacted various aspects of life, but its profound effects on the health sector are particularly striking because of its cutting-edge nature. Mobile computing characteristics enable IoT to play a more important role when used with mobile computing. A significant part of the benefits of IoT in healthcare can be attributed to mobile health, which is greatly enhanced by mobile computing. Wearables transmit large amounts of data to IoT devices through sensors, actuators, and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…To evaluate the efficiency of our proposed SBAODV scheme, we compared it with several other routing protocols, including low-power and noisy routing protocol (LPNRP) [32], tree protocol for healthcare (TPH) [41], a routing protocol for healthcare (RPH) [42], fuzzy dynamic trust-based routing protocol (FDTRP) [43], and dual attack detection routing protocol (DADRP) [44]. We assumed a reactive gateway as the IoMT gateway in the network and simulated the network for 600 s using a constant bit rate (CBR) traffic model and UDP application.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the efficiency of our proposed SBAODV scheme, we compared it with several other routing protocols, including low-power and noisy routing protocol (LPNRP) [32], tree protocol for healthcare (TPH) [41], a routing protocol for healthcare (RPH) [42], fuzzy dynamic trust-based routing protocol (FDTRP) [43], and dual attack detection routing protocol (DADRP) [44]. We assumed a reactive gateway as the IoMT gateway in the network and simulated the network for 600 s using a constant bit rate (CBR) traffic model and UDP application.…”
Section: Methodsmentioning
confidence: 99%
“…M Al-Amin et al [26] proposed a framework for sentimental analysis using some reviews on the internet. Refaee et al [27]suggested a system for IoT-based secure and scalable healthcare data transmission that is based on an improved routing protocol.Rajagopal et al [28] investigated the potential effects of arti cial intelligence systems on business results using a mix of consumer choice and the matching principle. In terms of entrepreneurship, the study showed that arti cial intelligence systems can aid in improved decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [15] proposed a secure and scalable framework for healthcare data transfer in the Internet of Things based on optimized routing protocols. First, health data from various IoT devices such as wearable and sensors is collected.…”
Section: Literature Reviewmentioning
confidence: 99%